Blood Glucose Level of Hyperglycemia Rats (Rattus novergicus) after Neem Gum (Azadirachta indica) Administration - Utami, Eva Tyas; Fajariyah, Susantin; Lelono, Asmoro; Nihayah, Husnatun (Jurnal Biologi Tropis, 2025)
Neem, a member of the Meliaceae family, is recognized to have the ability to decrease blood glucose levels. The study’s goal is to determine the neem gum (NG) impact in overcoming hyperglycemia in Wistar rats. There were three groups of rats in this study: (1) control, (2) hyperglycemic group (which got Streptozotocin (STZ) treatment but not NG treatment), and (3) hyperglycemic group (which got STZ treatment and 15% NG treatment) for three weeks. The T test results revealed notable variations before and after giving STZ. The finding indicated the blood glucose level before STZ induction in control was 86.50 ± 3.15 mg/dL, and the diabetic rat group (treated with STZ) was 87.60 ± 4.56 mg/dL. After STZ induction (7th day), there was a noteworthy rise in amount of glucose, namely 435.34 ± 120.33 mg/dL compare to the STZ treatment. The Duncan Multiple Range (DMRT) test showed there is no discernible difference between the STZ and NG treatments; however, there was a downward trend on days 14, 21, and 28. The conclusion of this study is that 15% NG has failed to decreas ehyperglycemia to normal blood glucose levels.